The susceptibility to fosfomycin of Gram-negative bacteria isolates from urinary tract infection in the Czech Republic: data from a unicentric study - Fajfr, Miroslav; Louda, Miroslav; Paterová, Pavla; Ryšková, Lenka; Pacovský, Jaroslav; Košina, Josef; Žemličková, Helena; Broďák, Miloš (BMC urology, 2017)
BACKGROUND: Against a background of rapid increase of β-lactamase-producing or multi-resistant pathogenic bacteria and the resulting lack of effective antibiotic treatment, some older antibiotics have been tested for new therapeutic uses. One of these is fosfomycin, to which according to studies these resistant bacteria are very sensitive. Our study was designed because there is no data on the fosfomycin susceptibility rate in the Czech Republic. METHOD: In this study from January 2013 to June 2014 3295 unique isolates of Gram-negative bacteria which had caused urinary tract infections were examined. The antibiotic susceptibility was measured by disk diffusion test. Both EUCAST and CLSI guidelines criteria (for fosfomycin only) were used for the antibiotic susceptibility evaluation. RESULTS: The most frequently tested bacterial isolates were Escherichia coli (51.3%, n = 1703), Klebsiella pneumoniae (19.4%, n = 643) and Proteus spp. (11.8%, n = 392). Among all isolates 29.0% (n = 963) were resistant to fluoroquinolones, 11.3% (n = 374) produced extended spectrum β-lactamase and 4.2% (n = 141) produced AmpC β-lactamase. The overall in vitro susceptibility was significantly higher for fosfomycin compared to the other tested per-oral antibiotics (nitrofurantoin, ampicillin, co-trimoxazole, ciprofloxacin and cefuroxime) against all tested Gram-negative rod isolates (excluding Morganella morgani and Acinetobacter spp. isolates). Fosfomycin also remained highly active against those isolates with extended spectrum β-lactamase (ESBL) production (95.8% in Escherichia coli isolates and 85.3% in Klebsiella pneumoniae isolates), unlike other tested per-oral antibiotics, which showed significant (p < 0.0001) susceptibility decrease. CONCLUSION: We have confirmed in the Czech Republic the very high susceptibility to fosfomycin trometamol of urinary tract infection pathogens, particularly Gram-negative rods including those producing β-lactamase.
Keywords: beta-Lactamases; Česká republika; fosfomycin; infekce močového ústrojí; Microbial Sensitivity Tests; lidé; Gram-Negative Bacteria; gramnegativní bakterie; mikrobiální testy citlivosti; antibakteriální látky; Anti-Bacterial Agents; Urinary Tract Infections; Czech Republic; beta-laktamasy; Fosfomycin; Humans